Chimaeric HBV core particles carrying a defined segment of Puumala hantavirus nucleocapsid protein evoke protective immunity in an animal model - Ulrich, Rainer G.; Lundkvist, Åke; Meisel, Helga; Koletzki, Diana; Brus Sjölander, Katarina; Gelderblom, Hans R.; Borisova, Galina; Schnitzler, Paul; Darai, Gholamreza; Krüger, Detlev H. (Vaccine, 1998)
Hantaviruses are rodent-born agents which are pathogenic in humans causing haemorrhagic fever with renal syndrome or hantavirus pulmonary syndrome. To induce a protective immunity against a European hantavirus (Puumala) we constructed chimaeric hepatitis B virus (HBV) core particles carrying defined fragments of the Puumala virus nucleocapsid protein. After immunisation of bank voles, the natural host of Puumala virus, with core particles possessing an insertion of the N-terminal part of Puumala virus nucleocapsid protein, four of five animals were protected against subsequent virus challenge. The results show that the major protective region of the nucleocapsid protein is located between amino acids 1 and 45 and that chimaeric HBV core-like particles are useful carries of foreign protective epitopes.
Gesehen am 05.09.2024